2017
DOI: 10.1080/19396368.2016.1267820
|View full text |Cite
|
Sign up to set email alerts
|

Age-related changes in gene expression patterns of immature and aged rat primordial follicles

Abstract: Women are born with millions of primordial follicles which gradually decrease with increasing age and this irreversible supply of follicles completely exhausts at menopause. The fertility capacity of women diminishes in parallel with aging. The mechanisms for reproductive aging are not fully understood. We have observed a decline in Brca1 mediated DNA repair in aging rat primordial follicles. To further understand the age-related molecular changes, we performed microarray gene expression analysis using total R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 64 publications
1
12
0
Order By: Relevance
“…MiRNA are differentially expressed during ageing in a tissue-specific manner in both humans and rodents 2932 , suggesting that these molecules modify target genes that are active in ageing-related pathways 32 . Ageing was also linked to a substantial alteration in gene expression in various tissues of mammals and human 14,3335 . Comprehensive analysis of transcriptomic activities indicated a differential expression of mRNA across the life cycle of the rat in various organs 21 .…”
Section: Discussionmentioning
confidence: 99%
“…MiRNA are differentially expressed during ageing in a tissue-specific manner in both humans and rodents 2932 , suggesting that these molecules modify target genes that are active in ageing-related pathways 32 . Ageing was also linked to a substantial alteration in gene expression in various tissues of mammals and human 14,3335 . Comprehensive analysis of transcriptomic activities indicated a differential expression of mRNA across the life cycle of the rat in various organs 21 .…”
Section: Discussionmentioning
confidence: 99%
“…The gradual decrease of both the quantity and the quality of the oocytes surrounded by the granulosa cells in all stages of follicles dominates the reproductive aging [4]. In previous study, Govindaraj et al revealed that gene expression patterns changed considerably in the rat primordial follicles in the process of ovarian aging [25]. Folliculogenesis in the ovary is a highly dynamic and periodic process regulated by both intra- and extra-oocyte factors [26].…”
Section: Discussionmentioning
confidence: 99%
“…In other genetic systems, it has been reported that several RNA species play critical roles in the regulation of ovarian physiology, and these RNA species are involved in protein-coding RNAs [7981] and noncoding RNAs such as miRNAs [1214] and lncRNAs [15, 16]. The current study presents the global transcriptome expression profile of ovarian aging and identified a large number of differentially expressed RNAs.…”
Section: Discussionmentioning
confidence: 91%